Pengaruh Relational Benefits Terhadap Kepuasan Pelanggan Dalam Meningkatkan Loyalitas Pelanggan Studi Kasus Pada Pengguna Aplikasi Grab - Virgo Simamora; Juita Verawati (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2021)
This study aims to determine the Effect of Relational Benefit on Customers in increasing Loyalty. Relational Benefit is the dependent variable in this study. Further data analysis using smart PLS. The population in this study are Grab users in the Cilincing Village, North Jakarta. The number of samples in this study were 100 Grab users using purposive sampling. The results of this study indicate that Relational Benefit has a significant positive effect on Customer Loyalty, Relational Benefit has a significant positive effect on customers, Furthermore, Relational Benefit has a significant positive effect on Customer Loyalty through customer goals.Keywords: Relational Benefit, Customer Satisfaction, Customer Loyalty